Optimalisasi Aplikasi Powtoon Sebagai Media Presentasi Interaktif Untuk Meningkatkan Kinerja Pada PT. Jaya Persada Indonesia - Mohammad Badrul; Cahyani Budihartanti; Laila Septiana; Yumi Novita Dewi (Abditeknika Jurnal Pengabdian Masyarakat, 2023)
PT. Jaya Persada Indonesia, merupakan sebuah perusahaan yang bergerak dibidang usaha pengembangan property yang professional. Untuk memberikan inspirasi bagi karyawan PT. Jaya Persada Indonesia (JPI), JPI menghadirkan program pelatihan yang lebih intensif dan terpadu yang disebut dengan JPI Incubator Bisnis. Dalam memberikan pelatihan, presentasi yang tampilkan terlalu monoton sehingga kurang menarik perhatian para peserta. Berdasarkan latar belakang tersebut, paran Dosen dari Universitas Nusa Mandiri telah memberikan pelatihan kepada para karyawan dengan tema “Optimalisasi Penggunaan Aplikasi Powtoon Sebagai Media Presentasi Yang Interaktif Untuk Meningkatkan Kinerja Pada PT. Jaya Persada Indonesia”, Diharapkan dengan adanya pelatihan yang telah dilaksanakan dapat menambah wawasan para karyawan dalam penggunaan aplikasi Powtoon dalam membuat presentasi yang menarik, sehingga dapat menarik para klien lebih banyak lagi. PT. Jaya Persada Indonesia, is a company engaged in the business of professional property development. To provide inspiration for employees of PT. Jaya Persada Indonesia (JPI) presents a more intensive and integrated training program called JPI Incubator Business. In delivering and presenting the material, the appearance of the presentation is too monotonous so that it does not attract the attention of the participants so that the material presented is not conveyed properly. Based on this background, the lecturers from Nusa Mandiri University took the initiative to provide training to employees with the theme Optimizing the use of the Powtoon application as an interactive media presentation to improve performance at PT. Jaya Persada Indonesia. The method used in this training activity is in the form of lectures delivered by tutors, discussions or questions and answers according to problems in the field and their solutions. The purpose of this training is to increase the knowledge and ability of employees to make attractive media presentations with the Powtoon application which combines text, audio and visuals in the form of animation with various features that can be accessed online so that employees can make and present more attractive presentations because presenting the material is not too long without reducing the content of the material delivered to the participants so that it can attract the participants to focus on the material presented so that the material can be well received by the participants.